34 Use of the DECAF score to facilitate early discharge for acute exacerbation of COPD patients: a quality improvement project at a district general hospital. (16th November 2020) - Light, Alexander; Donaldson, Callum; Khatana, Usman; Nizar, Zanil; Nadeem, Iftikhar
Abstract : Aims: DECAF is a scoring tool that can predict the severity of patients attending hospital with an acute exacerbation of chronic obstructive pulmonary disease (AECOPD). Previous research has shown AECOPD patients with DECAF scores of 0 and 1 are candidates for early discharge. Using quality improvement methodology, we aimed to implement a DECAF protocol at our hospital and assess its effect on short-term patient outcomes. Methods: Plan-do-study-act (PDSA) methodology was used. Patients attending Bedford Hospital with AECOPD and a DECAF score of 0 or 1 were included. For September 2019, notes were retrospectively reviewed for patients for DECAF score, length of stay, 30-day re-admission and 30-day mortality (PDSA cycle 1). A framework to facilitate early discharge for patients was subsequently established. Awareness was increased through teaching sessions, posters and targeted emails. To evaluate the impact of our improvements, data for the same parameters were then collected prospectively (PDSA cycle 2). Results: DECAF score was assessed for no patients in PDSA cycle 1 (n=20) but was assessed for all patients in PDSA cycle 2 (n=14). Number of days stay in hospital was significantly decreased in PDSA cycle 2 (mean 0.29±0.45 days) compared to PDSA cycle 1 (mean 3.71±2.69; difference p<0.00001). 30-day re-admission was not significantly different between PDSA cycles 1 and 2 (p=0.50). No patient in either PDSA cycle experienced mortality within 30 days of discharge. Conclusion: Implementing a DECAF protocol is safe and feasible in the district general hospital setting and can facilitate early discharge for patients with low severity AECOPD. Additional recruitment and further study of patient outcomes is required.